Landscape design as an added value to real estate development in Klang Valley - Mohd. Hussain, Mohd. Ramzi; Tukiman, Izawati; Zen, Ismawi (Trans Tech Publications, Switzerland, 2014)
The aim of the paper is to investigate the importance of landscape design in the planning and designing of a residential property in Klang Valley. It has been proven that proper landscape planning and design with the sustainable concept and approach help to create conducive and responsive environment of residential properties. The paper employed quantitative approaches which includes i) a questionnaire survey; and ii) an observation. This empirical study is based on the findings of case studies conducted on several residential areas in Klang Valley. The findings show that the residents have very clear ideas both on how much green space is really important in residential areas in order to create a sustainable residential environment. Despite the absence of public actions in terms of providing information, encouraging participations in the survey and promoting awareness by those interviewed have shown considerable interest in promoting landscape design to be applied in real estate development. The perceptions of the quality and quantity of landscape designs in residential areas and how landscape design can influence the values of real estate developments especially in Klang Valley can be further researched for future study.